Crystal structure of methyl 8-hydroxy-3-isopropyl-5a,8-dimethyl-2,3,4,5,5a,6,7,8,10a,10b-decahydrocyclohepta[e]indene-3a(1H)-carboxylate, C21H34O3 - Brito Iván; Bórquez Jorge; Simirgiotis Mario; Cárdenas Alejandro; Molina-Salinas Gloria M.; Jerz Gerold; Peña-Rodriguez Luis Manuel; Winterhalter Peter (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C21H34O3, orthorhombic, P212121 (no. 19), a = 7.5420(7) Å, b = 11.6929(11) Å, c = 22.657(2) Å, V = 1998.1(3) Å3, Z = 4, Rgt(F) = 0.0383, wRref(F2) = 0.113, T = 293(2) K.